Implementation of Kanban Method in Transactional System Design in the “Mr. Sneakers” Shoe Laundry Business - Puspitarani, Yan; Violina, Sriyani; Rumaisa, Fitrah; Sulianta, Feri (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Laundry information system design using Kanban method is a strategic step to improve operational efficiency and responsiveness to customer needs in the laundry business. The study aims to design an information system that is integrated with the Kanban method to optimize the transaction process from receiving orders to returning to customers. The study outlines the process of designing a laundry information system using Kanban principles, including workflow mapping, suitable Kanban board design and integration with existing information systems. The results of this information system design show that the application of Kanban can provide a clear visualization of the workflow in the process, improve operational efficiency by speeding up the order cycle time, reducing waiting times, and minimizing errors in the transactions process. Good integration between the information system and the Kanban board allows managers to monitor order status in real time and respond quickly to changing customer requests. In conclusion, designing a laundry information system using the Kanban method can improve business performance, strengthen customer relationships, and create significant added value.